Platelet P2Y12 receptor antagonist pharmacokinetics and pharmaco -dynamics: A foundation for distinguishing mechanisms of bleeding and anticipated risk for platelet-directed therapies - Becker, Richard C.; Gurbel, Paul A. (Thrombosis and Haemostasis, 2010)
The platelet P2Y12 receptor is involved in all aspects of arterial thrombosis, including adhesion, activation, aggregation, secretion and development of a stable aggregate on which coagulation proteins can assemble and fibrin strands can mesh. Inhibition of the P2Y12 receptor has been shown convincingly to reduce cardiovascular events among patients with acute coronary syndromes (ACS) and in patients undergoing percutaneous intervention (PCI). Current studies are exploring whether there is a threshold of platelet aggregation below which only more bleeding occurs, without a concomitant reduction in clinical events. The following review considers the potential relevance of reversible and irreversible mechanisms of P2Y12 inhibition to bleeding risk, posing the question, “Is it not only how much but how a platelet P2Y12 receptor is inhibited that determines the attributable safety profile?”
Keywords: Platelet P2Y12 receptor; clopidogrel; prasugrel; ticagrelor; cangrelor